1993
DOI: 10.1111/j.1365-2842.1993.tb01514.x
|View full text |Cite
|
Sign up to set email alerts
|

The oral status of elderly removable partial denture wearers

Abstract: A random sample of 1019 elderly home dwelling persons participated in this study. There were 809 dentate respondents, 28.6% of whom wore removable partial dentures. They were examined for coronal and root caries, gingival recession, pocket depth and loss of gingival attachment. The removable partial dentures were also evaluated. Abutment teeth were found to be more likely to have caries and periodontal disease than all other teeth. Using a MANOVA statistical procedure, the analysis indicated that the partial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 20 publications
5
62
1
4
Order By: Relevance
“…3,4 Further, cross sectional studies and longitudinal clinical trials have reported an increased incidence of caries and periodontal breakdown when RPDs are worn. [5][6][7][8] This appar ent poor compliance with wearing RPDs, together with their potential to generate an additional long-term treatment need, represents a considerable potential waste of resource within the NHS. The reasons for this discrepancy are unclear but may reflect the attitudes and expectation of patients, the clinical knowledge and technique of dentists, or administrative and financial restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Further, cross sectional studies and longitudinal clinical trials have reported an increased incidence of caries and periodontal breakdown when RPDs are worn. [5][6][7][8] This appar ent poor compliance with wearing RPDs, together with their potential to generate an additional long-term treatment need, represents a considerable potential waste of resource within the NHS. The reasons for this discrepancy are unclear but may reflect the attitudes and expectation of patients, the clinical knowledge and technique of dentists, or administrative and financial restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos sobre o efeito da prótese parcial removível na saúde periodontal têm mostrado que os dentes envolvidos no desenho da prótese desenvolvem signifi cati vamente mais doença periodontal que aqueles não incluídos no planejamento 2,5,9 . O uso da PPR leva a mudanças prejudiciais na qualidade e quanti dade de formação e acúmulo de biofi lme dentário ao redor dos dentes remanescentes 8 , contudo, se for manti da boa higiene oral, existi rá pouco ou nenhum dano aos dentes remanescentes e seus suportes periodontais 5,15 .…”
Section: Discussionunclassified
“…Sugerindo que uma proservação mais prolongada poderia responder em longo prazo, se realmente a prótese dentomuco-suportada traria maiores danos para os dentes pilares do que a prótese dento-suportada. Usuários de próteses com problemas têm signifi cati vamente escores de recessão gengival e perda de inserção superior aos usuários de próteses sem problemas 9 . Isso indica que não a prótese por si só, mas a prótese defeituosa é que pode provocar diferença na condição periodontal e até perda de inserção.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bergman et al, 10 have shown that such prostheses are not likely to contribute to dental disease if well maintained. However, workers such as Berg 11 and Drake and Beck 12 suggest that partial denture wearers are often not meticulous in the care of their dentures, and, therefore, experience increased levels of caries and periodontal disease. These studies show that abutment teeth for partial dentures are particularly prone to periodontal attachment loss and root caries.…”
Section: Removable Partial Denturesmentioning
confidence: 99%